The emotions of graduating medical students about prior patient care experiences. Issue 3 (March 2015) - Clay, Alison S.; Ross, Elizabeth; Chudgar, Saumil M.; Grochowski, Colleen O'Connor; Tulsky, James A.; Shapiro, Dan
Highlights Graduating medical students express a range of emotions in written reflections. Emotions towards patients include gratitude and sorrow for their suffering. Disappointment centers on inability to cure, work-life balance, and hierarchy. Students' ability to cope mirror skills of self-efficacy for patients. More reflective writing and focus on wellness may ultimately improve patient care.